BEHAVIORISTIC CONDITIONING IN PHILANTHROPIC TAHFIDZ EDUCATION: A CASE STUDY OF UNDERPRIVILEGED SANTRI AT PESANTREN HABIBURROHMAN BANDUNG - Jamil Abdul Aziz; Ade Abdul Muqit; Fuji Zakiyatul Fikriyah; Ismi Rahmayanti (Academic Bright Collaboration, 2026)
This study investigates the implementation of behavioristic conditioning in tahfidz education within a philanthropic pesantren serving exclusively yatim (orphaned) and dhu’afa (economically disadvantaged) santri. It examines how philanthropic mechanisms function as enablers of learning readiness and how they interact with behavioristic principles in shaping memorization outcomes for underprivileged learners. Employing a qualitative single-case study design at Pondok Pesantren Tahfidz Al-Qur'an (PPTQ) Habiburrohman, Bandung, data were collected through purposive sampling involving institutional leaders, tahfidz instructors, and santri. Instruments included semi-structured interviews, participant observation of ziyadah, muroja’ah, and daily activities, as well as analysis of institutional documents. Data were analyzed using Miles and Huberman’s interactive model with source, method, and time triangulation. Behavioristic conditioning is systematically applied through the ziyadah-muroja’ah system (Law of Exercise), reward and ta’zir mechanisms (operant conditioning), and fixed daily scheduling (classical conditioning). The full-scholarship philanthropic model effectively removes financial barriers, creates psychological readiness (Thorndike’s Law of Readiness), and fosters gratitude-based intrinsic motivation that complements external reinforcement. The single-site case study limits generalizability beyond similar philanthropic tahfidz institutions. The absence of longitudinal data on post-graduation hafalan retention further constrains the findings. This research is the first to examine behavioristic conditioning specifically in a philanthropic tahfidz setting for yatim and dhu’afa santri. It introduces the concept of “philanthropic readiness engineering,” highlighting Islamic philanthropy as a behavioral intervention that enhances conditioning effectiveness for vulnerable populations.